Analysis of research on Foreign Language Translations of the Epopee «The Path of Abay» - Sadykova, Roza; Turlybekov, Berdibay; Kanseitova, Ulbossyn; Tulebayeva, Kuralay (Opción, 2018)
The present paper investigated the translation of the Kazakh science and M. Auezov's story about the nature of research on foreign language translations of the novel-epopee "The path of Abay". The paper also noted that the story of the Kazakh writer, Mukhtar Auezov's novelepopee "The path of Abay", which was translated into other languages, was still going on throughout the history of the Kazakh steppe in the history of the Kazakh literature, and the comparative linguistic translation of the epic translated "The path of Abay" into other languages.